Hej!
Zadanie 8 :
7 - ½(5 - 3x) = (2x - 1) + 3(x - 6) / * 2
14 - (5 - 3x) = 2 * (2x - 1) + 6 * (x - 6)
14 - 5 + 3x = 4x - 2 + 6x - 36
9 + 3x = 10x - 38 / - 10x
9 + 3x - 10x = -38 / - 9
3x - 10x = -38 - 9
-7x = -47 / : (-7)
x = 6 i 5/7
Zadanie 9 :
2(x - 2) = 6 - 3(x + 5)
2x - 4 = 6 - 3x - 15
2x - 4 = -3x - 9
2x + 3x = -9 + 4
5x = -5 / : 5
x = -1
4x - 2 = 3(x - 1)
4x - 2 = 3x - 3
4x - 3x = -3 + 2
x = -1
3 - 2x = ⅓(x + 2) / * 3
9 - 6x = x + 2
-6x - x = 2 - 9
-7x = -7 / : (-7)
x = 1
7x - 4 = 3x - 8
7x - 3x = -8 + 4
4x = -4 / : 4
x = -1
Tylko równanie C ma inne rozwiązanie
Pozdrawiam! - Julka